Ideal redox behavior of the high-density self-assembled monolayer of a molecular tripod on a Au(111) surface with a terminal ferrocene group - Kitagawa, Toshikazu (Langmuir : the ACS journal of surfaces and colloids, 2013)
A dyad consisting of a tripod-shaped trithiol with an adamantane core and a terminal ferrocenyl group linked through ap-phenyleneethynylene bridge was synthesized. The trithiol formed a stable self-assembled monolayer (SAM) on Au(111), wherein each molecule is bound to the surface by three-point adsorption using all sulfur atoms, with confirmation by PM-IRRAS and XPS analyses. Cyclic voltammetry of the SAM showed a line shape typical of an ideal adsorbed system, that is, a monolayer with negligible electrostatic interaction among the terminal ferrocenyl groups. Thus, a rare SAM was achieved, in which the component molecules were isolated from adjacent molecules without the coadsorption of nonelectroactive molecules